Pengembangan Sistem Informasi Manajemen Pengelolaan Kearsipan di Lembaga Jaminan Sosial - Dhea Perdana Coenraad; Imam Heryanto; Haris Nurdiansyah; Jimmy Rusjiana (Majalah Bisnis & IPTEK, 2021)
This study aims to see to what extent the effectiveness of an information system that has just been implemented in a social security institution where this system is a replacement for the previous system which is considered less effective in managing archives. Based on the results of research and testing, it was found that this new system has a better effectiveness value and a far more optimal level of accuracy in archiving management.